Intraprocedural cone-beam CT with parenchymal blood volume assessment for transarterial chemoembolization guidance: Impact on the effectiveness of the individual TACE sessions compared to DSA guidance alone. Issue 140 (July 2021) - Peisen, Felix; Maurer, Michael; Grosse, Ulrich; Nikolaou, Konstantin; Syha, Roland; Artzner, Christoph; Bitzer, Michael; Horger, Marius; Grözinger, Gerd
Highlights: The study findings support the use of PBV-CBCT for DEB-TACE guidance. PBV-CBCT leads to a considerable increase of the treatment efficiency. PBV-CBCT guidance has no negative effects on tumour response and overall survival. PBV-CBCT helps to avoid unnecessary re-interventions. Abstract: Purpose: The objective of this retrospective single centre study was to evaluate the impact of intraprocedural cone-beam CT with parenchymal blood volume assessment (PBV-CBCT) for guidance of transarterial chemoembolization with drug-eluting beads (DEB-TACE) in HCC patients on the effectiveness (local tumour response, survival and number of individual TACE sessions) compared to guidance solely by digital subtraction angiography (DSA). Method: n = 179 HCC patients (mean age, 77.4 y) undergoing DEB-TACE, with (n = 28) and without (n = 151) PBV-CBCT, using 100−300 μm microspheres loaded with epirubicin were retrospectively analysed. Tumour response according to mRECIST, overall survival and number of TACE interventions as well as laboratory parameters for liver function and inflammation were recorded. The analysis of the influence of intraprocedural PBV-CBCT was based on matched pair analysis (CBCT n = 28 vs. DSA n = 28). Gender, tumour number, tumour size and HCC risk factors were equally distributed between both groups. Results: Response rates according to mRECIST: CBCT : PD: 7%, SD: 28 %, PR: 46 %, CR: 18 %; DSA : PD: 7 %, SD: 32 %, PR: 39 %, CR: 21 % (p = 0.174). Median OS: CBCT : 44.1 months; DSA : 28.8 months (p = 0.815). Median TACE number: CBCT : 2.0; DSA : 3.0 (p = 0.046). Conclusions: The use of intraprocedural PBV-CBCT for TACE guidance reduced the number of re-interventions, with no negative effects on tumour response and overall survival. The study findings support the use of PBV-CBCT for DEB-TACE guidance as the improved immediate feedback leads to a considerable increase of the treatment efficiency and helps to avoid unnecessary re-interventions.